Rezension von: Wiesflecker, Hermann, Kaiser Maximilian I., Bd. 1 + 2 - Wunder, Gerd (Württembergisch Franken, 1985)
Hermann Wiesflecker: Kaiser Maximilianl. München: Oldenbourg. Bd. 1, 1977, 622 S.; Bd. 2, 1981, 691 S.